Developing Letter to Sound Correspondences through Controlled Dictation Practice in a Sudanese Classroom - Ali, Ezzeldin Mahmoud; Ashareef, Zuhayra (ELT Worldwide: Journal of English Language Teaching, 2025)
This paper attempts to measure how pupils at primary schools benefit from controlled dictation practice in the learning of letter-to-sound correspondences. The paper targets primary-school pupils of English as a Foreign Language in Sudanese classrooms. An experimental approach was adopted in which pre- and post-tests were carried out for data collection from pupils before and after training. There were two types of tests which included (i) citation forms test (recorded) and (ii) a short text test. For prevention of replication of the same test items, the study used different test items in the pre-and post-tests of both citation forms and sentence-embedded words. Moreover, as the experimental group per se is not sufficient for the production of credible results, the study used a control group. As usual, unlike the experimental group, the control group took both pre-and-posttests without receiving any intervention. The findings indicate that the pupils' scores following training conducted through controlled practice surpass their pretest scores. This observation suggests that controlled dictation practice positively influences the development of pupils' abilities to connect letters with their corresponding sounds. The findings also revealed that pupils demonstrate greater success in associating English letters with their corresponding sounds when engaging in dictation practice with isolated words, rather than when these words are incorporated into sentences. The reason behind this difficulty is likely because pupils experience difficulty in linking the spelling of words to their phonetic sounds within sentences. Interestingly, dictation proves to be a good practice activity integrating listening and writing, which gives pupils a considerable opportunity to listen and write down words or text being read to them by their testers. The transition from controlled to free dictation practice aids pupils in solidifying their understanding of letter-sound relationships. Dictation practice tool is beneficial as it aids pupils in comprehending the word through auditory recognition and contextual spelling.